Kieślowski in Spain: History, Reception and Inspiration - Bardzińska, Joanna (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2019)
The films of Krzysztof Kieślowski arrived in Spain comparatively late, and when they did so this was mainly due to the Film Festivals at San Sebastián and Valladolid, as well the efforts of independent producers like the brothers José María and Miguel Morales of Wanda Films. In 1988, A Short Film About Love was presented at the San Sebastián Festival, where it won the Special Prize and the FIPRESCI Prize, and caught the attention of Spanish critics. To this day, Kieślowski remains the Polish director best-known to the Spanish – as was made clear in 2016, by the numerous events and screenings marking the 20th anniversary of his death. There can be no doubt that, in the homeland of Buñuel, no other Polish director evokes as much enthusiasm. Considering the Spanish reaction to the maker of the Three Colours, this article focuses on the distribution of Kieślowski’s works in Spain, as well as the director’s presence at the Spanish Festivals. Further subjects of analysis are reviews by Spanish critics and the state of research into Kieslowski’s creative output in the Spanish language, as well as the release of his films on DVD and Blu-Ray. The above focus on festivals, the attitudes of critics, and the popularity among the Spanish viewing public is supplemented by a study of the impact of Kieślowski’s output on the work of Spanish directors, as well as efforts to discern the direct influence of the former’s films in offering the latter inspiration.